2020
DOI: 10.1038/s41598-020-63606-3
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: Circulating microRNAs are associated with incident diabetes over 10 years in Japanese Americans

Abstract: Epigenetic changes precede the development of diabetes by many years, providing clues to its pathogenesis. We explored whether the epigenetic markers, circulating microRNAs (miRNAs), were associated with incident diabetes in Japanese Americans. We conducted a pilot study (n = 10) using plasma from age-and sex-matched participants who did or did not develop diabetes in the Japanese American Community Diabetes Study, an observational study of diabetes risk factors. Extraction and high-throughput sequencing of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The miR-199a is also increased in serum of patients with type 2 diabetes mellitus (T2DM) and inhibits GLUT4 expression in vitro (Yan et al, 2014). Serum miR-4732 has also been linked with diabetes in humans (Wander et al, 2020 a LogFC: difference of the mean of logarithm of the of fold change of the compared groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-199a is also increased in serum of patients with type 2 diabetes mellitus (T2DM) and inhibits GLUT4 expression in vitro (Yan et al, 2014). Serum miR-4732 has also been linked with diabetes in humans (Wander et al, 2020 a LogFC: difference of the mean of logarithm of the of fold change of the compared groups.…”
Section: Discussionmentioning
confidence: 99%
“…The miR‐199a is also increased in serum of patients with type 2 diabetes mellitus (T2DM) and inhibits GLUT4 expression in vitro (Yan et al, 2014). Serum miR‐4732 has also been linked with diabetes in humans (Wander et al, 2020). As previously mentioned, IGHD individuals have high insulin sensitivity with low insulin concentrations (Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent high throughput plasma sequencing study revealed the down-regulation of three of the circulating miRNAs present in the identified meta-signature (hsa-miR-15b-5p, hsa-miR-106b-3p, hsa-miR-106b-5p), in association with incident T2D [38]. Multiple studies attest to the upregulation of hsa-miR-33b-5p in circulatory and adipose tissues in the presence of dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, myomiRNA-7, myomiRNA-96, and myomiRNA-124a have been recognized to alter pancreatic β-cell [42,43], while myomiRNA-26, myomiRNA-148, my-omiRNA-182, and myomiRNA-483 stimulated insulin gene transcription [44,45]. Recently, a short report showed that circulating miRNAs with functions in skeletal muscle (miRNA-106b and miRNA-20b-5p) were associated with development of diabetes [46]. Those data are related to Japanese American cohort as epigenetic marker for diabetes development [46].…”
Section: Skeletal Musclementioning
confidence: 99%
“…Recently, a short report showed that circulating miRNAs with functions in skeletal muscle (miRNA‐106b and miRNA‐20b‐5p) were associated with development of diabetes [46]. Those data are related to Japanese American cohort as epigenetic marker for diabetes development [46]. Changes in miRNA releases by the muscle could be implicated in pancreas dysfunction and the progression of T2D.…”
Section: Circulating Organ‐specific Mirnas During T2dmentioning
confidence: 99%